Comprehensive program of increase of efficiency of locomotive park JSC RZHD - P. N. Rubezhanski; A. V. Davydov (Вестник СибАДИ)
The authors propose a comprehensive program of unification into a single system all processes of the life cycle of locomotives that reduce costs associated primarily with the operation and maintenance of a locomotive fleet of JSC "Russian Railways". The main indicator of this complex system is the level of technical readiness of the product, determined by availability. The developed methodology will allow to move from a technology fixation to a technical failure, with subsequent identification of their causes and recovery, technologies of prediction and prevention of these failures is based on the constant control of technical condition of locomotives and forecasting of the stock of the resource in the Online mode.